Social benefit cost analysis of ecosystem-based climate change adaptations: a community-level case study in Tanna Island, Vanuatu. (2nd July 2020) - Buckwell, Andrew; Ware, Dan; Fleming, Christopher; Smart, James C. R.; Mackey, Brendan; Nalau, Johanna; Dan, Allan
ABSTRACT: Small island developing states are vulnerable to the impacts of climate change, including more intense and frequent extreme weather, warming temperatures, coastal erosion, inundation, and coral bleaching. Locally-specific natural resource threats, associated with population growth and tourism, exacerbate these systemic risks, which are particularly acute where community well-being is subsistence-based and directly reliant on ecosystem services. Garden productivity is falling as the cropping/fallow cycle intensifies and culturally and there is loss of observance of traditional resource taboos, eroding the effectiveness of customary management. Ecosystem based adaptations (EbA) provide a fruitful range of interventions and are beginning to attract development funding. We undertook a social benefit cost analysis for a suite of interconnecting EbAs for Tanna in Vanuatu. We found that funds targeted at increasing the productivity of the gardens returns significant social benefit. This also reduces pressure on natural resource threats and can potentially be adopted by all households on Tanna. In addition, increasing the community's capacity to balance formal forest and reef conservation with customary management can provide small, but nevertheless important complimentary benefits. Our programme design included interlinking activities, including a series of demonstration garden plots, extension officers, community radio, a community ranger programme and a tree nursery.